Study of beluga (Huso huso) Farming in Brackish Water Earth Pond - Alizadeh, Morteza; Nafisi, M.; Tahoory, H.; Sarsangi, H.; Dashtkyan, K. (Iranian Fisheries Science Research Institute, 2007)
This research was conducted for evaluation of adaptation and growth rate of beluga (Huso huso) in brackish water earth pond in Yazd Province. In order to select the best density for beluga culture in brackish water earth pond, beluga with initial average weight of 21g were stocked 0.4 and 0.8 peace/m2 of earth pond with 1000m2 in area. Water resource was a semi deep well with initial temperature and salinity of 24 and 11.5 g/l respectively. During the time of culture, water temperature, pH, DO and salinity were 12-27 , 8.1-9.4, 4.5- 8.9mg/l and 11.5-13g/l in respectively. Culture period was 240 days. Results showed that growth performance of fishes in studied treatments had no significant difference. Iranian Fisheries Science Research Institute Published